Modulatory effects of orexin and dynorphin on stress-related alcohol seeking and relapse: pivotal role of the posterior paraventricular nucleus of the thalamus - Holguin, Gabriel; Martin-Fardon, Rémi (Frontiers in Pharmacology, 2026)
Alcohol use disorder (AUD) remains a significant problem in the United States, resulting in over 178,000 alcohol-related deaths annually. A central problem in treating AUD is the high rate of relapse to alcohol use even after protracted periods of abstinence. Stress is a major contributor to the chronic relapsing and compulsive nature of AUD, and it alters neurocircuitry mediating craving and drug seeking. Chronic alcohol use dysregulates the neuropeptides orexin (OX)/hypocretin and dynorphin (DYN), which contribute to alcohol seeking and relapse. OX neurons originate exclusively in the hypothalamus and co-express DYN. Although OX and DYN are localized in the same synaptic vesicles and co-released when the hypothalamus is stimulated, they play opposing roles in reward, motivation, and substance use. OX, via OX receptor (OXR) signaling, promotes reward-seeking behavior, whereas DYN, acting through κ-opioid receptors (KOPs), increases depressive-like states and plays a key role in mediating aversive effects of stress. OX neurons densely innervate the paraventricular nucleus of the thalamus (PVT), a brain region that is involved in the regulation of reward function, stress, anxiety, and drug-directed behavior. In individuals with AUD, chronic alcohol use damages the thalamus, resulting in volume reductions and cognitive deficits. Therefore, lasting changes in PVT OX/DYN transmission and their interaction following chronic alcohol use may underlie stress-induced alcohol craving and relapse. Although their opposing roles in the PVT are established, implications of their interaction, particularly under conditions of stress, are limited in the context of alcohol use and reinstatement. This review synthesizes evidence from preclinical evidence and complementary clinical observations that implicate the co-transmission of OX and DYN in the PVT, with an emphasis on the posterior PVT (pPVT), which receives the most OX afferents, during the stress-induced reinstatement of alcohol seeking. We also discuss the potential of targeting OXRs and KOPs pharmacologically to reduce stress-induced alcohol craving and reinstatement. This review will help disentangle individual vs. interactive contributions of OX and DYN, and elucidate how their modulation within stress- and reward-related circuits may reveal novel insights for preventing relapse in individuals with AUD.